Funding the future : philanthropy's influence on American higher education / Alison R. Bernstein. - Bernstein, Alison R., 1947-2016 (Rowman & Littlefield Education, a division of Rowman & Littlefield, 2014)
This book discusses the complex relationship of philanthropy to higher education both in historic perspective and in the present. It provides a road map for understanding philanthropy's influence on American higher education.